Students’ attitudes to social advertising: results of a study - A. N. Timokhovich; T. S. Filenko; A. S. Lelyakova (Цифровая социология)
The article presents the results of an empirical study aimed at studying the attitude of students to social advertising.   The object of the empirical study is student youth.   The subject of the study is the students’ attitude to the placement channels and modern technologies for attracting attention to social advertising.   The topic of social advertising was chosen for the study – advertising aimed at helping homeless animals. The study was conducted in spring 2023 using a survey method. The study identified young people’s readiness to be involved in solving social problems; the work showed young people’s attitudes to channels of social advertising; this research determined the attitudes to the emotional component of social advertising and revealed attitude to new ways of attracting attention that are used in contemporary social advertising. The study results indicate that, firstly, most young people are ready to help shelters and foundations that support to homeless animals, however, young people are not ready to make an effort to find the necessary information; secondly, young people do not always notice social advertising, despite the fact that they actively use different media channels; thirdly, according to respondents, the most effective social advertising contains in the verbal or visual series direct encouragement to the target action; fourthly, in order to increase the level of involuntary attention of target groups to social advertising, it is necessary to use new techniques of visual impact on the audience using digital technologies. In conclusion of this article, findings and recommendations are formulated which can be applied in the development of social advertising campaigns.